THE INFLUENCE OF LIQUIDITY AND PROFITABILITY ON COMPANY VALUE IN THE MANUFACTURING SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) 2015-2019 - Imat Hikmat; Dwian Agustina; Fitria Haquei (AMAL INSANI (Indonesian Multidiscipline of Social Journal), 2022)
This research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange (IDX). The purpose of this study is to find out the significant effect of the liquidity variable with the Current Ratio (CR) proxy and the profitability variable with the Return on Assets (ROA) proxy partially and simultaneously on firm value using the Price to Book Value (PBV) measuring instrument. The population in this study amounted to 150 manufacturing sector companies listed on the Indonesia Stock Exchange (IDX), using a purposive sampling technique which in the end, only nine companies were taken as samples. This study uses secondary data in annual financial statements from 2015 to 2019 by testing the hypothesis using multiple linear regression. The results of the partial study (T-Test) show that the liquidity variable has a sig value. 0.005 < 0.050 and the value of T count > T table (-2,985 > 2.018) has a significant negative effect on firm value. while profitability has a sig value. 0.410 > 0.050 and the value of T count < T table (0.833 < 2.018) has no significant effect on firm value. And the results of simultaneous research (F-Test) M has a value of F count and F table, namely (5.515 > 3.220) and a significance value (0.007 < 0.050), indicating that liquidity and profitability together have a significant effect on firm value. Keywords: Liquidity; Profitability; Firm Value.